Resorcylic Acid Lactones in Urine Samples of Croatian Farm Animals. Issue 2 (6th October 2018) - Vulić, A; Lešić, T; Kudumija, N; Mikuš, T; Pleadin, J
Abstract: Metabolic transformation of zearalenone (ZEA), a mycotoxin which can contaminate both food and feed, results in the formation of five metabolites, one of them being zeranol (α-ZAL), which can be abused in farm animals as a growth promoter. To the best of our knowledge, there is no analytical method that can distinguish whether α-ZAL is present in an animal urine sample as a result of ZEA biotransformation or as a result of anabolic abuse. This study aimed at monitoring resorcylic acid lactones (RALs) concentration in urine of farm animals over several years. Six hundred and three cattle and pig urine samples were collected on farms in different Croatian regions and analyzed for RAL presence. Based on the testing results, all RAL-positive samples were considered to be consequential to feed contamination. The difference in primary ZEA metabolites' ratio (α-zearalenol/β-zearalenol) was observed between cattle (0.03–0.41) and pig (2.05–17.39) urine samples. If the animals are treated with α-ZAL and fed on ZEA-contaminated feed, α-ZAL and taleranol found in their organisms could come from two sources, so that the reliability of the statistical model might be questionable. Based on these findings, there exists the need for improving the approach to the distinction between α-ZAL abuse and ZEA feed contamination.